Clinical characteristics and optical coherence tomography findings in epiretinal membrane, macular pseudohole, epiretinal membrane-foveoschisis, and lamellar macular hole - Noriko Kubota; Kazunori Miyata; Yosai Mori; Yuji Nakano; Hitoshi Goto; Fumiki Okamoto (PLoS ONE, 2025)
Purpose To evaluate the optical coherence tomography (OCT) findings of epiretinal membrane (ERM) and its three associated diseases: macular pseudohole (MPH), ERM-foveoschisis (ERM-FS), and lamellar macular hole (LMH). Methods We retrospectively reviewed all eyes that underwent vitrectomy with a follow-up of at least 6 months. All eyes were classified into four groups, ERM, MPH, ERM-FS, and LMH based on spectral-domain (SD) OCT findings. Factors analyzed included preoperative and postoperative best-corrected visual acuity (BCVA), presence of inner and outer retinal cysts, epiretinal proliferation (EP), and ellipsoid zone (EZ) disruption, central fovea thickness (CFT), central retina thickness (CRT), and macular volume (MV). Results After enrolling 720 eyes of 664 patients, eyes were classified into four groups: ERM (592 eyes), MPH (76 eyes), ERM-FS (63 eyes), and LMH (42 eyes). BCVA significantly improved in all groups. Although preoperative BCVA was not significantly different among the four groups, postoperative BCVA was significantly worse in LMH versus ERM (p < 0.001). Inner and outer retinal cysts were significantly more prevalent in ERM-FS versus ERM and the other three groups, respectively. EP was significantly more frequently observed in LMH versus the other three groups (p < 0.001). CFT and CRT were significantly higher in ERM versus the other three groups, and MV was significantly larger in ERM than in MPH and LMH (p < 0.05). Conclusion ERM had a higher CFT and CRT, and a larger MV. The postoperative BCVA was worse in LMH versus ERM, while LMH had a higher frequency of EP.